Effect of Zinc Oxide nanoparticals preparation from Zinc Sulphate (ZnSo4) against gram negative or gram positive microorganisms in vitro - S, Khitam S.; E.D, Alhtheal; J.B., Azhar (The Iraqi Journal of Veterinary Medicine, 2018)
This research aims to prepare ZnO NPs by using chemical bath deposition way from ZnSO4 and NaOH as starting materials. It was examined by X-ray diffraction, Scanning Electron Microscopy, Zeta potential and Fourier Transformation Infrared. Scanning Electron Microscopy images showed various morphological changes of ZnO nanoparticles obtained by the above method and the different magnification Scanning Electron Microscopy images of the nanoparticle and confirms that the Nano flowers are grown with well-defined morphology and diameters varying between 60-110 nm. The effect of Zinc oxide nanoparticles against bacteria staphylococcus aureus, E.coli and Pseudomous aeruginosa showed the ability of this substance to inhibit the growth of all types of bacteria in different concentrations. The percentage of survival bacteria was (2, 3.7 and 6%) for E.coli bacteria and (1, 1.5 and 5 %) for Pseudomous aeruginosa bacteria, while the percentage was (0.8, 1 and 1.5 %) for staphylococcus aurous respectively for all concentration.